2015
DOI: 10.1089/apc.2015.0156
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Trust in Physicians and Trust in the Healthcare System on Linkage, Retention, and Adherence to HIV Care

Abstract: Lack of trust by the patient in the physicians or the healthcare system has been associated with poorer health outcomes. The present study was designed to determine if trust in physicians and the healthcare system among persons newly diagnosed with HIV infection was predictive of patients' subsequent linkage, retention, and adherence to HIV care. 178 newly diagnosed HIV infected patients were administered the trust-in-physicians and trust-in-healthcare system scales. Median trust-in-physicians and trust-in-hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 29 publications
(40 reference statements)
2
51
0
1
Order By: Relevance
“…Trust in physicians correlates positively with adherence to treatment recommendations, perceived effectiveness of care, and improvement in self‐reported health . Patients with CRS report a wide range of TPS scores, with results comparable to those in patients with other chronic diseases . The association between trust in physicians and treatment outcomes among patients with chronic disease have been evaluated previously.…”
Section: Discussionmentioning
confidence: 97%
“…Trust in physicians correlates positively with adherence to treatment recommendations, perceived effectiveness of care, and improvement in self‐reported health . Patients with CRS report a wide range of TPS scores, with results comparable to those in patients with other chronic diseases . The association between trust in physicians and treatment outcomes among patients with chronic disease have been evaluated previously.…”
Section: Discussionmentioning
confidence: 97%
“…45 There have also been studies associating improved trust in clinicians and disclosure of disease status with better clinical retention, evaluated immediately after linkage to care. 46,47 However, as ART initiation is now universally recommended, the events of linkage and ART initiation are converging, making these conclusions germane to a broader population. It has also been shown that patients feeling well or experiencing a loss of interest in their own healthcare are more likely to encounter discontinuities in care.…”
Section: Discussionmentioning
confidence: 99%
“…This included patient access to providers via telephone and text, allowing providers to directly communicate with patients outside of operating hours, and fostering a caring, non-judgmental philosophy toward patients. Patient trust in providers has been associated with increased patient satisfaction with care (McCoy, 2005) and improved retention in care (Dang et al, 2013; Graham et al, 2015; Kempf et al, 2010). Patients want providers who connect with them, validate them as individuals, and partner with them to optimize their HIV care (Mallinson, Rajabium & Coleman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Successful patient engagement and retention in HIV care has been facilitated by (a) enhanced personal contact with providers (Gardner et al, 2014) and patient trust in physicians, including perceptions of provider respect (Dang, Westbrook, Black, Rodriguez-Barradas & Giordano, 2013; Graham, Shahini, Grimes, Hartman, & Giordano, 2015; Maulsby et al, 2015; Yehia et al, 2015); (b) intensive case management to alleviate disparities and increase access to care providers (Bradford, 2007; Maulsby et al, 2015; Mugavero, Amico, Horn, & Thompson, 2013); and (c) housing assistance to improve access to health care and use of health care services (Wolitski et al, 2010). Enhancing provider communication, including increased empathy for the experiences of patients that influence care, better listening skills, and cultural competency can positively impact engagement and retention in HIV care, including keeping appointments and adherence to ART (Christopoulos et al, 2015; Flickinger 2013, 2016; Saha 2010).…”
mentioning
confidence: 99%